Polyoma Virus Infection of Retinoic Acid-Induced Differentiated Teratocarcinoma Cells - Fujimura, Frank K. (1981)
The mouse teratocarcinoma stem cell line, F9, becomes permissive for productive polyoma infection upon treatment with retinoic acid. Through the use of M13-polyoma recombinant single-stranded DNA probes, spliced and unspliced early viral RNA were detected after polyoma infection of retinoic acid-treated and untreated F9 cultures.